2016
DOI: 10.2166/nh.2016.217
|View full text |Cite
|
Sign up to set email alerts
|

Modifying Hargreaves–Samani equation with meteorological variables for estimation of reference evapotranspiration in Turkey

Abstract: The Food and Agriculture Organization advocates the Penman–Monteith (FAO-56 PM) equation as the standard model for estimation of the reference evapotranspiration (ET0) because it is considered to have better accuracy. However, in regions where meteorological variables such as solar radiation, wind speed, and relative humidity are not gauged, the Hargreaves–Samani (HS) equation is resorted to as an alternative simply because it needs minimum and maximum air temperatures only as the explanatory variables. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 46 publications
2
27
0
1
Order By: Relevance
“…Due to the simple operability of regression models, practitioners have widely used the simple linear regression model in many studies, as can be found in Mallikarjuna et al [14], Wen et al [3], Peng et al [15], Cobaner et al [16], Citakoglu et al [17], and Huo et al [10]. The regression model expresses the dependence of a response parameter on many independent parameters and is used in modeling a varied range of hydrologic process studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the simple operability of regression models, practitioners have widely used the simple linear regression model in many studies, as can be found in Mallikarjuna et al [14], Wen et al [3], Peng et al [15], Cobaner et al [16], Citakoglu et al [17], and Huo et al [10]. The regression model expresses the dependence of a response parameter on many independent parameters and is used in modeling a varied range of hydrologic process studies.…”
Section: Introductionmentioning
confidence: 99%
“…Chauhan and Shrivastava [20] investigated the performance of reference evapotranspiration in India using climate-based models and ANNs and found that the ANN models performed better than the climatic-based models in all performance indices. Despite the higher accuracy of the computer algorithms, these algorithms must be implemented through specific software, and the models with particular inputs of climatic factors could not be expressed in straightforward mathematical expressions like the empirical models [16]. Thus, the empirical model as an alternative option to estimate the ET 0 has been recommended in many other studies [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…For humid regions, however, Paredes et al [38] documented that wind impacts are unimportant for the HS model, but require proper adjustments. To surpass the limitations that the absence of wind speed may impose in tropical and semiarid regions, Cobaner et al [11] assessed a modified version of the HS model for 275 weather stations in Turkey. The authors modified version included the wind speed in the equation, resulting in better accuracy for all stations.…”
Section: Performances Of Improved Hargreaves-samani Modelsmentioning
confidence: 99%
“…Para la estimación de la ET0 en regiones donde las mediciones meteorológicas son escasas, la ecuación de HS se puede utilizar con mayor precisión [8].…”
Section: Evapotranspiración De Referencia (Et0)unclassified